Determinación de las bases para construir un modelo de explicación de la deslocalización empresarial a través de la revisión de los principales trabajos empíricos - Jesús F. Lampón Caride (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2011)
Location Theory and its different approaches have been the support of the empirical studies on relocation in the last years. However, this support has been exclusively implicit with frequency. This is because most of the works have ignored the neoclassical, behavioural or institutional theoretical basis, approaching from an empiricist point of view based on common sense the introduction of potentially important variables in the relocation decisions. The result is the existence of innumerable variables that could have some effect - even occasional or marginally - on the relocation probability. In order to build a parsimonious model that adheres to the golden rule of any econometric analysis keep it simple, we will do an exhaustive review of the recent work on relocation. By doing this, we will describe, sort and group the used variables and recognize the determinants of explanation of the international relocation phenomenon.
Keywords: F2; R3; 330; location theory; international relocation; relocation factors